Hubungan Usia, Beban Kerja, Posisi Tubuh, Dan Aktivitas Fisik Terhadap Kejadian Low Back Pain Pada Perawat Pelaksana Di RS EMC Sentul Tahun 2023 - Bayu Aditya Trisnaning Kasih (Pusat Riset dan Inovasi Nasional, 2023)
Nurses have a high risk of developing low back pain because in carrying out their duties nurses make many movements such as bending, lifting and pushing loads in a way that is not ergonomic. The prevalence of nurses experiencing low back pain in Indonesia is 31% in 2018 and 57% in 2019. Internal factors related to low back pain are age, workload, body position, and physical activity. This study aims to determine the relationship between age, workload, body position and physical activity with the incidence of low back pain among nurses at EMC Sentul Hospital in 2023. The type of research is quantitative. The research design used was a cross-sectional study. The sampling technique used simple random sampling technique. The sample in this study amounted to 55 people. The results of this study are that there is a significant relationship between age ((pvalue = 0.014 <0.05), workload (pvalue = 0.013 <0.05), body position (pvalue = 0.005 <0.05), physical activity (pvalue = 0.036 <0.05) with the incidence of low back pain in implementing nurses at EMC Sentul Hospital in 2023. For this reason, in carrying out work, it is important to prioritize occupational safety and health so that they can work productively and avoid the risk of low back pain and other work-related diseases.